Tuberculous myocarditis: A report of two cases - S. Ratanarapee (2018)
Two cases of tuberculous myocarditis are here described. The first case, an 86-year-old woman, had apparently had 'cryptic miliary tuberculosis' for about one year, but this was unrecognised until full-blown disease appeared shortly prior to her death. The second case, a 23-year-old man, died of acute viral encephalitis, had noticeable gross lesions in the endocardium of the right ventricle. We believe that rare occurrence of myocardial tuberculosis is a true prevalence and is not caused by simple oversight. That scarcity of tuberculous myocarditis is a matter of organ susceptibility and resistance is discussed.